2018
DOI: 10.5152/turkjsurg.2018.3881
|View full text |Cite
|
Sign up to set email alerts
|

Approach to the diagnosis and treatment of mesenteric panniculitis from the surgical point of view

Abstract: Objective: To evaluate the diagnostic and treatment approaches for patients diagnosed with mesenteric panniculitis Material and Methods: We retrospectively reviewed all patients diagnosed with mesenteric panniculitis between January 2010 and March 2016. We recorded the demographic features, clinical symptoms, laboratory values, radiological methods, treatment approach, and outcomes of the patients. Results:We evaluated 22 patients (17 male and five female) with a mean age of 45.8±15.7 years. The most frequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Unlu et al [12] assessed 80 patients with MP and reported that the majority of these patients had a high BMI, and 57.5% were obese, 10% were morbidly obese, 17.5% were overweight, and 15% were normal weight. Kaya et al [15] reported in their study on the diagnosis and treatment of MP that 54.7% of patients with MP had a BMI of >30 kg/m 2 . The authors suggested that obesity might affect immunity and may be an underlying disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Unlu et al [12] assessed 80 patients with MP and reported that the majority of these patients had a high BMI, and 57.5% were obese, 10% were morbidly obese, 17.5% were overweight, and 15% were normal weight. Kaya et al [15] reported in their study on the diagnosis and treatment of MP that 54.7% of patients with MP had a BMI of >30 kg/m 2 . The authors suggested that obesity might affect immunity and may be an underlying disorder.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristic CT findings of mesenteric panniculitis, the most frequent form of intra-abdominal panniculitis, include a tumoral pseudocapsule (a fatty mass separated from the base of the mesentery), an adipose ring (a normal adipose tissue surrounding the mesenteric vessels), and an intra-abdominal mass displacing the adjacent bowel loops without invasion ( 6 - 8 ). Grenier et al reported characteristic findings of panniculitis of the greater omentum on CT as an encapsulated heterogeneous mass of fatty density with fibrous bands and fascial thickening ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice and in the literature other anti-inflammatory, immunosuppressive and immunomodulatory drugs are used such as thalidomide, cyclophosphamide, progesterone, colchicine, azathioprine, tamoxifen, antibiotics and emetine, or even radiotherapy. In severe cases or as a diagnostic procedure in differentiation from other causes of abdominal symptoms such as perforation or bowel obstruction surgical procedures may be necessary [10].…”
Section: Discussionmentioning
confidence: 99%